Changes in prevalence and epidemiology of female genital cancers in northeastern Iran in a 35-year study - Seyede Samaneh Hoseini; Zohreh Yousefi; Maryam Emadzadeh; Fatemeh Homaee Shandiz; Parvin Hokmabadi; Mahta Salehi; Pardis Shojaei; Maryam Salehi (Mashhad University of Medical Sciences, 2020)
Introduction: Gynecologic cancers are the important cause of women's mortality in the world. Considering the importance of epidemiological recognition of gynecologic cancers in regional form for planning the preventive measures, this study was performed with aim to assess the epidemiologic characteristics of patients with gynecologic cancers referring to Mashhad oncologic centers in 1982-2016. Methods: In this cross-sectional study, after evaluation of all patients' files recorded in the last 35 years, the required data were extracted and recorded. The study period was categorized into 4 intervals: before 1990, 1991-2000, 2001-2010, and 2011-2016. The relative frequency, mean age at the time of diagnosis, and the 35-year trend were then assessed. Data were analyzed by SPSS software (version 16) and Chi-Square, Anova, and Scheffe tests. P Results: Among 2953 studied patients, mean age was (49.32 ± 13.69 years. The highest mean age was observed among the patients with uterine body neoplasms (52.21±12.49) and the lowest mean age in those with ovarian cancer (46.09±16.09). The mean age at the time of diagnosis of ovarian cancer has significantly increased in the last decades (p<0.001) while decreased in those with cervical cancer (p=0.017). Cervical and ovarian cancers had the highest relative frequency during the entire study period (39.3% (1161 cases) and 36.6% (1080 cases), respectively). There was also a significant difference in the frequency of various cancers across different decades (p<0.001). Conclusion: Cervical cancer was the most frequent neoplasm in this study. The mean age of diagnosis had increased in patients with ovarian cancer and decreased in cervical cancer. Since cervical cancer can be controlled by preventive measures, more attention to screening of this cancer is recommended.